CAMBODIAN BUDDHIST MONK STUDENTS’ MOTIVATION IN LEARNING ENGLISH: THE CASE OF HUN NENG BUDDHIST PRIMARY SCHOOL, KAMPONG CHAM TOWN - Pheaktra Keo; Seylanin Yoeurn; Monyroth Prom; Pisith Chin; Sereyrath Em (Jurnal As-Salam, 2022)
This study presents an overview of a survey on Cambodian Buddhist monk students’ motivation in learning English at Hun Neng Buddhist Primary School, Kampong Cham Town. The study employed a quantitative method. The study aimed to examine the motivation levels of the participants and the difference between intrinsic and extrinsic motivation levels. 93 Buddhist monk students participated in the study. The findings show that the Buddhist monk students were highly motivated to learn English, and it was also reported that they were more extrinsically motivated than intrinsically motivated. The study also recommends that motivation inside and outside the classroom be carefully considered. It is also recommended that future research be conducted with a larger sample size using other statistical analyses at other educational institutions. Qualitative and mixed-methods designs are also recommended.